Estimate of the equilibrium moisture of wood Eucalyptus Spp. for the municipality of Montes Claros, Minas Gerais (Research, Society and Development, 2022)
The equilibrium moisture content of wood (EMU) inthe place where the wood will be applied is important so that its effects do not compromise the final use of the piece. Theobjectivewas to determine the EMU of Eucalyptus in a climatic chamber and compare them with Simpson's equation (1971), to determinethe extractive contents and their influence on the EMU. They used 42 samples of two clones, half were submitted to natural drying, the others to artificial drying and then arranged in the climate. The chamber was used to determine the EMU with conditions typical of the region and 's equation to estimate EMU from monthly averages of temperature and relative humidity (RH). To remove the extractives, it was applied three solvents: acetone, dichloromethane and milli-Q water. itobservedis in the results that the EMU averages had values closer to those estimated by the Simpson equation in conditions where the RH simulated was close to 72%, the proximity reduced as a function of the RH drop. With temperature, an effect similar to that of RH was noticed, as it was reduced the difference between the estimated and observed increased. Thesamples initially oven-dried showed EMU values closerto those estimated. Acetone was shown to have the highest extraction power. andIt is concluded that the mean values of EMU closer to those estimated bywere Simpson in conditions of higher temperature and RH 30°C 72 °%. The extractives showed behavior polar and the average EMU for Montes Claros was 12.42%.